The subject-spatial environment of higher educational institutions - one of ways of formation of design skills of students (Pedagogy of Higher and Secondary Education, 2007)
Forming of teaching of students in higher educational establishment, use of forms and methods which assist forming of professional aesthetic culture of future designers during organization of in-spatial environment of educational establishments.
Keywords: forming c f teaching; forming of professional aesthetic culture; organization of in-spatial environment